PELAKSANAAN ALIH MEDIA REKAM MEDIS DI FILING RSD KRMT WONGSONEGORO SEMARANG TAHUN 2024 - Pembayun, Yovita Manuella Kusuma; Setijaningsih, Retno Astuti (VISIKES, 2025)
Some patient medical record documents have not been transformed into electronic medical records at RSD KRMT Wongsonegoro Semarang. The purpose of this study was to describe the medical record media transfer in the Filing of RSD KRMT Wongsonegoro Semarang in 2024. This study is descriptive. The study collected data through interviews with two filing officers as responsible staff for medical record media transfer and the head of the Medical Record Department and observation of media transfer in March 2024. The analysis results were presented in a narrative. The results showed that the medical record media transfer is the filing officer's duty. Receipt of active outpatient medical records from polyclinics did not use expedition books. The number of active outpatient medical records that have been converted was unrecorded. Inactive medical record of inpatient alignment based on the sequence of medical record numbers in the last two group numbers on the inactive storage shelf. The unit has no Standard Operating Procedure (SOP) or Minimum Service Standard (MSS) for medical records media transfer. The Medical Record Department of RSD KRMT Wongsonegoro Semarang should establish a clear division of labor between filing officers and media transfer officers, create expedition features and a list for active outpatient medical record numbers that have been converted, rearrange inactive medical records storage for inpatients based on disease group and last date of treatment, add officers as validators of media transfer results, create SOPs and MMS for medical records media transfer, medical record retention, and destruction of medical records resulting of media transfer.